2021
DOI: 10.1002/ejoc.202100204
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones: Phytohormones with Promising Biomedical Applications

Abstract: Strigolactones are a class of carotenoid‐derived plant hormones, which impact many functions of plant metabolism in response to environmental stress. They also act as exogenous signals perceived by both mycorrhizal fungi and parasitic plants. The peculiar chemical skeleton of these molecules and their mode of action in plants inspired possible applications in biomedical fields. In this minireview, an overview of the most recent applications of Strigolactones and analog derivatives as anticancer, anti‐inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…In our experiment, the content of JA in the treatment groups was lower than that of the control group, indicating that small peptides and surfactants could down-regulate the expression of JA and delay the senescence of tea plants under high-temperature stress, playing a protective role on tea leaves. SL is also widely involved in plant stress [54][55][56][57][58][59]. Our results showed that small peptides and surfactants down-regulate the expression of SL and enhance the adaptability of tea plants under high-temperature stress.…”
Section: Discussionmentioning
confidence: 61%
“…In our experiment, the content of JA in the treatment groups was lower than that of the control group, indicating that small peptides and surfactants could down-regulate the expression of JA and delay the senescence of tea plants under high-temperature stress, playing a protective role on tea leaves. SL is also widely involved in plant stress [54][55][56][57][58][59]. Our results showed that small peptides and surfactants down-regulate the expression of SL and enhance the adaptability of tea plants under high-temperature stress.…”
Section: Discussionmentioning
confidence: 61%
“…PPIC is a cyclophilin which plays different roles in human health [54] , [55] , [75] . Antiviral and anticancer activities of natural or synthetic strigolactones have been documented [76] , [77] . Also, the activity of stereo-defined strigolactones has been acknowledged for high cancer cell specificity in humans [77] , [78] .…”
Section: Resultsmentioning
confidence: 99%
“…SLs are multifunctional plant metabolites acting as a class of hormones controlling plant developmental processes and interactions with other organisms (Lopez‐Raez et al ., 2017 ; Lanfranco et al ., 2018b ; Carvalhais et al ., 2019 ); they were even shown to have an impact on human cell lines as anticancer, anti‐inflammatory and antiviral drugs (Prandi et al ., 2021 ). SLs have therefore multiple target organisms, which, in turn, had to evolve a molecular machinery to perceive and respond to them.…”
Section: Discussionmentioning
confidence: 99%